PENGARUH KEBUTUHAN AKTUALISASI DIRI,DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU SEKOLAH DASAR DI KECAMATAN MIJEN KOTA SEMARANG - Imron, Muh (Students Journal of Economic and Management, 2012)
The purposeof this research is to axammine and analize the influence self actualization of teacher perfomance, work disciplin, work motivation of teacher performance. This research do for all of the teacher of Elementary School that were civil cervant with III and IV grade in UPT Disdikpora of Mijen District, Semarang Regency, with 108personsampelaccountas a respondence. The source data is a prime data. Variable measured use to likert scale with the seven answer alternative. This research is explanatory research. The data analysis preparation used to regresimetode. The research model show variable influence the headmaster leadership and teacher competence of teacher performance with Adjusted R2=0,547. The hipothersexaminator result show that the headmaster leadership not influence in significance manner of teacher performance. Key word :Self Actualization, work discipline, work motivation, and teacher performance.